The Effect of Cross Training Style On The Development of Some Physiological Indicators In Youth Futsall - Jassim, Mouyad (Journal of Physical Education, 2016)
The importance of the study lies in using modern styles and apparatuses in training to develop the results of futsall teams. The problem of the research lies in weaknesses in training programs that do not meet the needs of players in physical fitness. The aim of the research was to identify the effect of training according to cross training style in some physical variables in futsall. The researchers used the experimental method; the subjects were youth futsall players. The researchers specified the physiological indicators (metabolic level before and after effort, maximum oxygen uptake and special oxygen endurance). The researchers' designed a training program. The data was collected and treated using proper statistical operations to come up with the results. The researchers concluded that cross training develop some physical and motor abilities and some physiological indicators in youth futsall players.